GAMIFICATION IN HIGHER EDUCATION: EXPERIENCE OF POLAND AND UKRAINE - Jakub Głowacki; Yelizaveta Kriukova; Nataliya Avshenyuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
Open access to modern information technologies generates a new type of society that increases the productivity and competitiveness of any country in the world market and requires significant changes in the education system. One of the most innovative approaches in education is gamification of learning which has considerable capabilities to increase students' enjoyment, interest and engagement in the study. In this regard, the aim of our research is to analyse the use of gamification in higher education institutions of Poland, Ukraine and to study the effectiveness of using Kahoot as one of gamification technologies in teaching English for specific purposes (ESP) to students in a technical university. As shown by the results of the study, Poland has considerable experience in the use of computer games in higher education, whereas Ukraine is only beginning to implement these technologies in learning. An experimental study of the use of Kahoot platform in ESP classes at university level, which employed the methods of testing, observation and questioning, showed the effectiveness and expediency of this technology, as the students demonstrated a higher achievement rate, more active engagement and deeper motivation for learning.